2016
DOI: 10.1371/journal.pgen.1006125
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analyses in 128,266 Individuals Identifies New Morningness and Sleep Duration Loci

Abstract: Disrupted circadian rhythms and reduced sleep duration are associated with several human diseases, particularly obesity and type 2 diabetes, but until recently, little was known about the genetic factors influencing these heritable traits. We performed genome-wide association studies of self-reported chronotype (morning/evening person) and self-reported sleep duration in 128,266 white British individuals from the UK Biobank study. Sixteen variants were associated with chronotype (P<5x10-8), including variants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
314
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(345 citation statements)
references
References 40 publications
28
314
2
1
Order By: Relevance
“…B 372: 20160246 can be well characterized. Extreme human chronotypes are commonly referred to as 'larks'-morning people (those who wake up early and are most alert in the first part of the day) and 'owls'-evening people (those who are most alert in the late evening hours and prefer to go to bed late) [145,146]. This descriptor of chronotype, used in epidemiological and association studies, has revealed a wealth of chronobiological information, including evidence for its partly genetic determination and its links to circadian mechanisms [147,148].…”
Section: (B) Chronotypementioning
confidence: 99%
“…B 372: 20160246 can be well characterized. Extreme human chronotypes are commonly referred to as 'larks'-morning people (those who wake up early and are most alert in the first part of the day) and 'owls'-evening people (those who are most alert in the late evening hours and prefer to go to bed late) [145,146]. This descriptor of chronotype, used in epidemiological and association studies, has revealed a wealth of chronobiological information, including evidence for its partly genetic determination and its links to circadian mechanisms [147,148].…”
Section: (B) Chronotypementioning
confidence: 99%
“…The teams utilized human genome DNA information from about 100,000 individuals whom they queried about their propensity to get up early or sleep in the morning. Interestingly, all three teams led to the same conclusion that genetic variants of RGS16 are closely associated with being a morning person [43][44][45]. These findings provide reason to suspect that RGS16-dependent similar circadian mechanisms operate in humans as well.…”
Section: The Scn-gene Project Identifies Rgs16 As a Gap Required Formentioning
confidence: 78%
“…Previous molecular genetic studies have begun to identify genetic variations related to sleep-wake behavior includes 3111 T/C SNP (rs1801260) of the Circadian Locomotor Output Cycles Kaput (CLOCK) gene (Benedetti et al, 2007) and variable-number tandem-repeat (VNTR) polymorphism of the period circadian clock 3 gene (PER3) (Viola et al, 2007). Also, there are a number of recent genome-wide association analyses (GWAS) studies on sleep quality and quantity (Lane et al, 2017;Jones et al, 2016;Byrne et al, 2013). Among the identified polymorphisms within the OPRM1 gene, 118A>G polymorphism is the most frequently studied in the literatures.…”
Section: Discussionmentioning
confidence: 99%